HAJATAN PERNIKAHAN: DARI NILAI-NILAI TRADISI DAN DAMPAK EKONOMINYA - Bayu Sudrajat (STAI Sufyan Tsauri Majenang, 2023)
Abstract Marriage is an important event in human life and carries many traditional values that are passed down from generation to generation. These traditional values reflect the cultural richness and social norms highly regarded in society. At the same time, wedding ceremonies also have significant economic impacts. This literature review aims to explore and analyze the relationship between the traditional values in wedding ceremonies and their economic impacts. The research methodology involves a literature review from various sources, such as academic journals, books, articles, and other relevant information sources. The findings of the research indicate that the traditional values in wedding ceremonies play a crucial role in preserving the cultural identity of a community. These traditions encompass customs, traditional attire, dances, music, local cuisine, and other practices that are inherited from generation to generation. Through these traditions, wedding ceremonies serve as a means to preserve and strengthen social bonds and the cultural sustainability of a community. Additionally, wedding ceremonies also have significant economic impacts. The preparations and execution of weddings involve the consumption of goods and services that contribute to local economic growth. This includes the purchase of wedding attire, food, decorations, photography, entertainment, and various other services. The increased consumption stimulates sectors related to weddings, creating job opportunities and increasing government revenue through taxes and related levies. Abstract Marriage is an important event in human life and carries many traditional values that are passed down from generation to generation. These traditional values reflect the cultural richness and social norms highly regarded in society. At the same time, wedding ceremonies also have significant economic impacts. This literature review aims to explore and analyze the relationship between the traditional values in wedding ceremonies and their economic impacts. The research methodology involves a literature review from various sources, such as academic journals, books, articles, and other relevant information sources. The findings of the research indicate that the traditional values in wedding ceremonies play a crucial role in preserving the cultural identity of a community. These traditions encompass customs, traditional attire, dances, music, local cuisine, and other practices that are inherited from generation to generation. Through these traditions, wedding ceremonies serve as a means to preserve and strengthen social bonds and the cultural sustainability of a community. Additionally, wedding ceremonies also have significant economic impacts. The preparations and execution of weddings involve the consumption of goods and services that contribute to local economic growth. This includes the purchase of wedding attire, food, decorations, photography, entertainment, and various other services. The increased consumption stimulates sectors related to weddings, creating job opportunities and increasing government revenue through taxes and related levies.